L'usage de « capsules post MOOC » et des podcasts à l'Université d'Abomey-Calavi - Serge Armel Attenoukon (Centre National d'Enseignement à Distance, 2017)
This paper presents the issue of a misuse in the knowledge mediation. Our investigation focuses on the role of Massive Open Online Courses (MOOC) data in the campus based teaching with a limited access to Internet and a poor energy availability. Considering the new policies supported with the goals to teach, learn and assess students differently, and also ensure the quality, what is the added value of the MOOC and especially the videos and podscats in the university pedagogy? Our investigation was based on a qualitative research with 61 individuals (students